Dialéctica de intelecto y voluntad en el conocimiento que el alma tiene de sí - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filosofía Alejandro Korn. Sección de Filosofía Medieval., 2002)
The paper discusses St. Thomas Aquinas' thought on the relationship between intellect and will in the act of speculatively knowing the spiritual nature of the human soul. It is claimed that the influence of Christian sources, particularly St. Augustine, allows Aquinas to conceive reflective knowledge originally. In it the will would not only influence the exercise of the intellect, but also its specification. Thus the will's adherence to certain objects would condition judgement about the nature of the ultimate operational principle of reflection. Knowledge of the self as spiritual subject would formally resolve itself into free willing.
Fil: Vázquez, Stella Maris. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.
Keywords: FILOSOFÍA MEDIEVAL; VOLUNTAD; ALMA; TOMÁS DE AQUINO, SANTO; AGUSTÍN, SANTO